(untitled) (Journal of the College of Languages (JCL), 2010)
The paper discusses the lack of a uniform definition of politeness due to the constant tension between its universality and language specificity, and argues that some of the theoretical debate could be resolved if the distinction between politeness as a commonsense notion and politeness as a theoretical construct were clearly addressed and acknowledged in the research.